ANALYSIS OF SUPPLY CHAIN MANAGEMENT METHODS IN RAW MATERIAL INVENTORY AND DISTRIBUTION OF CRIPS IN UD. BU SRI WEB-BASED - Anisa Indri; Nurwati; Nasrun Marpaung (Informatika, Universitas Jenderal Soedirman, 2022)
Bu'Sri was founded in 2006 to be precise on Jln. Baung Fish LK II Sidomukti, West Range. UD. Bu'Sri sells various types of chips such as Onion Cake, Peanut Cracker, Smooth Shrimp Crack and Banana Chips. So by implementing a Supply Chain Management system, you can manage a raw material inventory strategy to control the availability of these chips. Supply Chain Management is a management method, tool or approach that involves companies involved in supplying raw materials, producing goods, or sending them to final customers. With the problems that occur, it is necessary to have a special system that can be used to manage inventory and can monitor product inventory at each distribution and save the results of less traders. The problems faced so far need to find solutions to overcome the problems that occur by designing a web-based application user interface for raw material inventory and distribution of chips using the Supply Chain Management method, building supply chain management and using the PHP programming language and Mysql database. The results with this system make it easier for UD. Bu'Sri owners to manage suppliers or regulate the cycle of supply chain management, so that inventories can be fulfilled properly. And it is easier for consumers to find out what products are sold or marketed in the system according to the prices that have been determined by distribution in marketing. One way is to implement Supply Chain Management this strategy was chosen because it is seen as the most effective way to facilitate all parties involved and interested in the running of a production and can complete the empty gaps in the trading business strategy. The system to be designed is web-based.